2017
DOI: 10.1631/jzus.a1600325
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on critical equilibrium of trapped air pocket in water supply pipeline system

Abstract: A trapped air pocket can cause a partial air lock in the top of a hump pipe zone. It increases the resistance and decreases the hydraulic cross section, as well as the capacity of the water supply pipeline. A hydraulic model experiment is conducted to observe the deflection and movement of the trapped air pocket in the hump pipe zone. For various pipe flow velocities and air volumes, the head losses and the equilibrium slope angles are measured. The extra head losses are also obtained by reference to the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…The most comparable experimental study is that of Pozos-Estrada (2017), which investigated the transient interaction with large in-line air pockets followed by a hydraulic jump using a rapid solenoid movement, with the air found to reduce the transient amplitude and increase the transient period. Wan et al (2017) describes an experimental study to better understand the effect of in-line air pockets on flow dynamics and head losses at steady state. Previous work by Alexander et al (2020) for the in-line pocket scenario showed that the amplitude of the reflected wave could be accurately predicted using impedance theory, with larger pocket volumes resulting in increased reflectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The most comparable experimental study is that of Pozos-Estrada (2017), which investigated the transient interaction with large in-line air pockets followed by a hydraulic jump using a rapid solenoid movement, with the air found to reduce the transient amplitude and increase the transient period. Wan et al (2017) describes an experimental study to better understand the effect of in-line air pockets on flow dynamics and head losses at steady state. Previous work by Alexander et al (2020) for the in-line pocket scenario showed that the amplitude of the reflected wave could be accurately predicted using impedance theory, with larger pocket volumes resulting in increased reflectivity.…”
Section: Introductionmentioning
confidence: 99%
“…SRA et al [14] photographed and processed the stagnant gas phenomenon in the pipeline and established the generation law and movement state of stagnant gas in the pressurized pipeline. Wan et al [15] designed a physical test model with several consecutive bends and concluded through a large number of tests that an appropriate reduction in the inclination angle of the pipeline and an increase in the flow rate can effectively discharge the stagnant gas mass in the pipeline. Jansson et al [16] studied a pipeline water hammer with column separation in a flow range through physical tests.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously D5 can be used as the carrier [5,6]. Recently, H. Miao [7,9], D. Pu [10], W. Wan [11,12], and S. Li [13,14], etc., have reported new techniques of dyeing in D5 medium. In addition, R. Tao [15], X. Gao [16] have made researches about washing in D5 medium.…”
Section: Introductionmentioning
confidence: 99%